Audit of Surgery For Acute Appendicitis in National Medical College and Teaching Hospital, Birgunj - Yadav, Umesh Kumar; Bhatt, Pashupati Nath; NathMishra, Gorakha; Maharjan, Sunder; Gurung, Pramod (Journal of Nepalgunj Medical College, 2017)
Background: Acute appendicitis is one of the most common surgical emergencies in the world. The purpose of this study is to know clinical profile and outcome of surgery in patients with acute appendicitis. Materials and methods: This retrospective study was done in National Medical college and Teaching Hospital, Birgunj, Nepal from 2013 April to 2016 April. A total of 184 patients with suspected appendicitis who underwent surgery were included in the study. Patient's demographics, clinical features, white blood cell count, operative findings, histology report and outcome of surgery were recorded on patient's proforma. Results: Among 184 nd patients, 115 were males (62.5%) and 69 were females (37.5%). The majority of our patients were in the 2 decade (36.4%) followed rd by 3 decade (33.2%) with only 41.3% presenting within 24 hours of onset of symptoms. The most common symptoms were abdominal pain (100%), vomiting (68.5%), fever (37.5%) and history of migration of pain was present in 60.9%. Localized and generalized abdominal tenderness were present in 91.8% and 8.2% respectively. The most common incisions were gridiron (64.1%) and Lanz (27.2%). The negative appendicectomy rate was 9.2%. Acute appendiceal inflammation and gangrenous appendicitis was present in 69% and 4.9% respectively. The perforation rate was 16.8%. Post operative complications included surgical site infection (12.6%), complete wound dehiscence (1.1%) and chest infection (1.6%). The median length of hospital stay was 8 days. There was no mortality. Conclusion: Acute appendicitis is more commonly seen in young adults. Majority of patients present late in hospital. This delay presentation increases morbidity and treatment cost. JNGMC Vol. 14 No. 1 July 2016, Page: 2-4